PENGARUH PENILAIAN PRESTASI KERJA KARYAWAN TETAP TERHADAP PROMOSI JABATAN PADA PT. BANK BUKOPIN,Tbk. CABANG PALEMBANG - Riri Hanifa Anton Trianto Mahdi Hendri (Jurnal Manajemen Kompeten, 2019)
ABSTRACT This study aims to determine: (1) employee performance appraisal system at PT. Bank Bukopin, Tbk Palembang Branch, (2) the job promotion system at PT. Bank Bukopin, Tbk Palembang Branch, (3) the variable performance appraisal has a significant effect on the job promotion of PT. Bank Bukopin, Tbk Palembang Branch. The sample used in this study is permanent employees of PT. Bank Bukopin, Tbk Palembang Branch are 30 respondents, data obtained through questionnaires and document analysis. The sampling technique used is nonprobability sampling technique with purposive sampling method. The analytical method used is quantitative with associative approach using SPSS for Windows version 23.0. The results showed that the coefficient of determination R2 was 0.720, which means that the performance appraisal had a significant effect on job promotion by 72%, the remaining value of 28% was influenced by other variables not included in this study, namely the absence of vacancies or information of the intended position / higher level and do not have negative record. Keywords: performance appraisal, job promotion.